Analysis of the Implications of Burnout on the Subjective Well Being (Swb) of Employees at Pt Bank Rakyat Indonesia (Persero) Tbk. Head of Tanete Riaja Unit, Barru Regency - Nurdaeni (Pustaka Digital Indonesia, 2024)
This research is a type of qualitative research with the aim of knowing exactly the implications of burnout on subjective well-being among employees at PT Bank Rakyat Indonesia (Persero) Tbk. KCP Tanete Riaja Unit , Barru Regency . The type of data used is descriptive qualitative with data collection through observation and interviews. The research results that can be written show that employees at PT Bank Rakyat Indonesia (Persero) Tbk. Tanete Riaja KCP Unit, Barru Regency , experienced a Burnout condition which affected the Subjective Well Being condition which was classified as moderate when working. It is said to be moderate because looking at the Burnout dimension , researchers found that there are three indications that can influence it, namely overtime on Saturdays and Sundays, less time with family and stressful work aspects. Even though employees are experiencing moderate burnout , they still prioritize customer priorities by providing excellent service.